The effect of extract watery of Pomegranate peel on broiler infected with Escherichia coli experimentally - H.Habeb, Afrah (Al-Qadisiyah Journal of Pure Science, 2018)
This study was designed to determine the effect of extract watery of Pomegranate peel(Punica granatum)on broiler infected with Escherichia coli . In this study 100 chicks which were divided into two groups .The first group (25 chicks) given 5ml of sterile trypticase soya broth (control group) while the second group(75 chicks) given 5ml of trypticase soya broth which containing 2Ã—108CFU â„ ml of Escherichia coli(infected group).When the symptoms of infection were appearing extracting watery of Pomegranate peel was given at the concentrations 50 ,75 ,100 mg â„ml. The results showed a decreased in body weight , food - and water intake after infection and when we given the extract watery , there was an increase in body weight , food intake and the health of chicks according to the increased in concentration infused.